2023
DOI: 10.1097/md.0000000000032700
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of shear wave elastography for endometrial cancer: A meta-analysis

Abstract: Background: This meta-analysis aimed to identify the accuracy of shear wave elastography (SWE) in the diagnosis of endometrial cancer (EC). Methods: We searched the PubMed, Cochrane Library, and chinese biomedical literature database from inception to September 30, 2022. Meta-analysis was conducted using STATA version 14.0 and Meta-Disc version 1.4 software. We calculated summary statistics for sensitivity (Sen), specificity (Spe), positive and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, we could not find any studies on the diagnostic effectiveness of shear wave elastography for placental function. Generally, they focused on malignancy, mostly other systems, and fewer gynecological issues, commonly in endometrial cancer [46] and pelvic floor. [47] In this sense, performing our study with strain elastography instead of shear-wave elastography can be considered as the second limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we could not find any studies on the diagnostic effectiveness of shear wave elastography for placental function. Generally, they focused on malignancy, mostly other systems, and fewer gynecological issues, commonly in endometrial cancer [46] and pelvic floor. [47] In this sense, performing our study with strain elastography instead of shear-wave elastography can be considered as the second limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of placental elastography thickness predicting cholestasis and the distribution of the patients with and without cholestasis by determined cutoff value. focused on malignancy, mostly other systems, and fewer gynecological issues, commonly in endometrial cancer [46] and pelvic floor. [47] In this sense, performing our study with strain elastography instead of shear-wave elastography can be considered as the second limitation of our study.…”
Section: Tablementioning
confidence: 99%
“…13,14,17-19 Also a recent meta-analysis showed that SWE may have high diagnostic accuracy for the differential diagnosis of benign and malignant endometrial diseases. 20 In our study we also investigated the diagnostic performance of the shearwave elastography in endometrial cancer patients in terms of the histologic grade of the tumor. In our study, we found that patients with grade 3 EC had higher shearwave values compared to grade 1 and 2 patients 101.89 kPa, 13.52 kPa, 33.24 kPa, respectively (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature many studies conducted with transvaginal probe. 20,34 In this study we used abdominal real-time shearwave elastography. Abdominal wall fat has impact on measurement, so the impact of BMI on patients has not been studied, and it will be further explored in subsequent studies.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%